2022
DOI: 10.1177/1934578x221118547
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Traditional Chinese Medicine on Treatment of Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR), a common and blinding diabetic microvascular complication, is a harmful metabolic effect caused by persistent hyperglycemia. Owing to the complex pathogenesis of DR, various clinical treatment methods cannot completely prevent its development and are accompanied by various complications. Therefore, there is an urgent need to identify new therapeutic drugs or complementary and alternative therapies. Traditional Chinese medicine (TCM) has the unique advantages of multi-level, multi-tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Quercetin, a natural flavonoid abundant in the plant kingdom, exhibits anti-inflammatory and antioxidant properties. 15 Chai et al 16 have elucidated the therapeutic impact of quercetin in diabetic rats induced by streptozocin (STZ), showing significant improvements in ganglion cell count and retinal cell layer thickness. Quercetin also exhibited anti-inflammatory, anti-angiogenic, and neurotropic effects by downregulating inflammatory cytokines (IL-1β, IL-6, IL-18, TNF-α), NLRP3, TLR4, VEGF, and sICAM-1, while simultaneously upregulating HO-1, BDNF, and NGF in the retinal tissue of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin, a natural flavonoid abundant in the plant kingdom, exhibits anti-inflammatory and antioxidant properties. 15 Chai et al 16 have elucidated the therapeutic impact of quercetin in diabetic rats induced by streptozocin (STZ), showing significant improvements in ganglion cell count and retinal cell layer thickness. Quercetin also exhibited anti-inflammatory, anti-angiogenic, and neurotropic effects by downregulating inflammatory cytokines (IL-1β, IL-6, IL-18, TNF-α), NLRP3, TLR4, VEGF, and sICAM-1, while simultaneously upregulating HO-1, BDNF, and NGF in the retinal tissue of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, based on these bioactive compounds, with further structural modifications, these compounds are considered invaluable sources of potential therapeutic drugs, demonstrating the importance of identifying bioactive compounds. According to previous research conclusions ( Li W. C. et al, 2022 ), this review innovatively considers the core pathological mechanisms in the development processes of DR (such as inflammation, angiogenesis, and oxidative stress) as the fundamental unit and expounds on the mechanism and potential of TCM against DR from the perspective of signaling pathways ( Table 1 ). Inflammation plays a dominant role in the early stage of DR. TCM can improve inflammation through the NF-κB, MAPK/NF-κB, and TLR4/NF-κB signaling pathways against DR.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, many experimental studies have been conducted on TCM, which has demonstrated promising activity against DR. TCM is characterized by multiple components that act simultaneously on multiple targets in a synergistic manner to produce beneficial effects on the disease. The pathogenesis of DR is very complex, but after a long study period, scholars believe that the occurrence and development of DR are mainly related to inflammation, angiogenesis, oxidative stress, and apoptosis ( Li W. C. et al, 2022 ). Currently, there is a lack of system reviews on the signaling pathways of TCM against DR.…”
Section: Introductionmentioning
confidence: 99%
“…TCM can treat early DR based on syndrome differentiation, which has unique advantages in improving vision, delaying the progression of DR, promoting the improvement of pathological fundus changes, improving systemic symptoms, and enhancing the quality of life (Man and Sai, 2022;Liu et al, 2020;Li et al, 2022). Combining traditional chinese and western medicine can complement each other's strengths and weaknesses in treating early DR, leading to good clinical outcomes (Tejerina et al, 2015).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%